Clinical Spectrum and Management of Diabetic Ketoacidosis: Experience in A Tertiary Care Hospital (BIRDEM Medical Journal, 2012)
Background: Diabetic ketoacidosis (DKA) is an acute metabolic complication of diabetes mellitus (DM). It may be the presenting feature in type 1 DM, but more commonly it complicates previously diagnosed diabetic patients, both type 1 and type 2. If not recognized early and treated in a judicious way the outcome is often fatal. Objectives: The objectives of this study was to see the common presenting features of DKA, their precipitating causes, patterns of electrolyte imbalance, treatment requirement in early hours and to see the outcome. Materials and methods: This cross sectional study was done in BIRDEM General Hospital on fifty adult patients who presented with DKA over a period of nine months (January 2007 to September 2007). Results: Total number of patients were 50, male were 24 and female were 26 (M:F =12:13). Mean age was 27.6 ± 3.7 years. The incidence of DKA was more in known diabetic patients (32, 64%), in comparison with new cases (18, 36%). Frequency was more in poor village people (31, 62%). Vomiting (24, 48%) was the most frequent complaint, followed by fever (19, 38%), nausea (16, 32%), abdominal pain (14, 28%), weakness (13, 26%), polyuria (12, 24%) and polydypsia ( 8, 16%). Infection (18, 36%) was the most common precipitating cause, closely followed by inadherence to insulin therapy (17, 34%). In 12 (24%) cases no cause could be identified. Glycaemic control was poor, HbA1c was >7% in 98% cases. Severe acidosis (pH < 7) was less common (4, 8%) and gross electrolyte imbalance was uncommon but all patients required potassium supplementation in course of treatment. Neutrophilic leukocytosis was present in 44 (88%) cases, irrespective of presence of infection. Mortality was low (3, 6%). Conclusion: Diagnosis and treatment of DKA is not difficult if recognized early. So, high index of suspicion is necessary, particularly in previously undiagnosed cases. DOI: http://dx.doi.org/10.3329/birdem.v1i1.12380 Birdem Med J 2011; 1(1): 15-20